The study of personal finances at the university level (Research, Society and Development, 2019)
The objective of this study is to provide information on personal finance in the university public. The methodology used is qualitative, consisting of a non-university field study. As a result, the evidence that the existence of less knowledge about the subject, the importance of updating, and the use of an aid tool to understand their expenses, is a perspective of university students. Finally, the study concluded that students still do not have a way to save money, but intend in the future on the possibility of a reserve for eventual expenditure.